Expression of the water channel protein AQUAPORIN-4 in the brain during human liver cirrhosis - Shuliatnikova, T. V.; Tumanskyi, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (My University, 2022)
Hepatic encephalopathy (HE) is a frequent complication of liver cirrhosis, manifesting as a neuropsychiatric syndrome ranging from cognitive deficits to coma. HE pathophysiology is linked to elevated brain ammonia and neuroinflammation [1]. Astrocytes are central brain cells responsible for ammonia detoxification and during acute HE are characterized by severe swelling [1]. Aquaporin-4 (AQP4) is a central protein of astrocytes, predominant water channel in the brain, which undergo alteration in response to hyperammonemia [2].